The Potential of Microphysiological Systems for Artificial Intelligence Assisted Rapid Drug Discovery - Asif, Arun; Rahim Chethikkattuveli Salih , Abdul; Ricky, Zaroon (Journal of Intelligent Pervasive and Soft Computing, 2022)
The continuous evolution of deep learning tools with expanded applications in biology presents a great opportunity to improve drug analysis. The recent emergence of microphysiological tools has revolutionized the field of drug analysis owing to its human mimicking capacity. The convergence of artificial intelligence with automated microphysiological systems (MPS) may open the scope for speed-boosting drug discovery and development. Organ on a chip technology application at large scale will reduce the cost and time for the discovery of lead compounds for yet uncured diseases. The rapidly accumulated data from MPS-based analysis for new drug compounds with their initial indication will help in the elimination of the potentially irrelevant drugs at the earliest stage possible.